Technological Innovation Development On Carbon Dioxide Emission: Comparison Between China And India - Then, Tsze Yen (Universiti Malaysia Sarawak, (UNIMAS), 2022)
Purpose to achieve sustainable development and encountering the climate change are the challenges globally. This study examines the relationship between the carbon dioxide emission and technological innovation together with industrialization, economic growth and foreign direct investment in China and India. The current study is examined for period of 1985-2019. To estimate the short run and long run relationship of the variables, autoregressive distributed lagged model is applied for the analysis and estimation. The empirical results reveal that technological innovation is negatively affecting the carbon dioxide emissions and is significant in China for short run. Then, industrialization has implied significantly negative effect on the carbon dioxide emission in short run. Economic growth of both countries has positive impact and foreign direct investment in China has also positive effect on the carbon dioxide emission for short run estimation. Effect of all variables are significant in India whereas the variables except of technological innovation in long run. Cointegration is existed also in China as proven in ARDL bound test. This study found that there is causality in all the variables except for FDI in India meanwhile all the variables except for technological innovation have the causality in China. Policy suggested is focusing on the implementation of the green technology in economic activities and enhance the use of clean energy as for transition toward sustainable development of the nations.